IMPACTS OF CLIMATE CHANGE ON THERMAL BIOCLIMATIC INDICES OVER IRAQ - Y. K. Al-Timimi,; Alaa M. AL-Lami,; Firas S. Basheer,; Ammar Y. Awad, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate the trends in (11) thermal bioclimatic indicators throughout Iraq's various climates to better understand their spatiotemporal variations in different climates. All bioclimatic indicators have been calculated from daily ERA5 datasets of temperature extracted from 361 grid points covering Iraq. This data set covers global coverage of monthly temperatures from 1980 to 2022, with a spatial resolution of (0.25°x0.25°). Eleven thermal bioclimatic indicators were subjected to the Mann-Kendall (MK) test in order to measure trends in a single direction, without taking into account the influence of natural cycles. The findings showed that the majority of Iraq's thermal bioclimate indicators had changed. implying that rising temperatures have had a significant influence on the country's bioclimate. The annual mean temperature data revealed that Iraq had a considerable increase in Bio1 of (0.28 to 0.48) °C/decade, which is more than the )0.15( °C/decade worldwide average. The rise was found to be significantly greater in Iraq's northern and eastern regions. The analysis suggested that the diurnal temperature range decreased in most regions of Iraq, especially in the southern and northeastern sections. The maximum temperature increased most dramatically in the warmest quarter, whereas the changes in the coldest quarter were less noticeable, showing an increase in climatic extremes in Iraq. The study unequivocally shows that climate change is leading to an increase in the mean temperature, specifically during the warmest months of the year.